Armenian Melik‘s and Khojas of Transcaucasia during Nādir Shāh’s Rule - Kostikyan, Kristine («Մռավ» հրատ․)
After the wars waged against Ottomans in 1734-1736 Nādir Shāh succeeded in the annexation of the greater part of Transcaucasia to his state. The elite of the local Armenian population consisted of hereditary landlords (melik‘s) and wealthy merchants (khojas and bazzazes)11 once again after the fall of the Ṣafavid rule appeared under the rule of an Iranian state. Being representatives of a similar social group of Iranian society, Armenian meliks were acknowledged by Persian government and encouraged by Nādir to render him assistance during his wars against Ottoman forces in Iran and Transcaucasia. Nādir Shāh rewarded their major assistance with confirmation of their rights as meliks of some regions of Eastern Armenia and also few of them were appointed to high posts in local administration. However, Nādir's generosity ended shortly after his unsuccessful campaigns in Daghestan and western Transcaucasia in 1740s. The heavy taxes and tax extortion, also great fines put on wealthy Armenians and the Armenian Church resulted in their later estrangement from Nādir’s enterprises and lack of any cooperation with him. Inability to pay great fines and extra taxes was observed as signs of disobedience and resulted in persecutions exercised in respect of some representatives of the mentioned social groups. Հոդվածում քննվում են 18-րդ դարի հայ հասարակության վերնախավը ներկայացնող մելիքների և խոջաների սոցիալ-տնտեսական ու իրավաքաղաքական պատմության մի շարք հարցեր․ սկսած այդ եզրույթների ծագումից մինչև հայկական իրականության մեջ դրանց գործառական նշանակությունը, այդ սոցիալական խմբերի ներկայացուցիչների կապը և փոխհարաբերությունները պարսից իշխանությունների հետ և նրանց սոցիալ-քաղաքական դրության առանձնահատկությունները, դրանցում եղած փոփոխությունները տարածաշրջանում Նադիր շահի իշխանության հաստատումից մինչև անկում։
Keywords: History